PENGENALAN BANGUN DATAR MELALUI PENDEKATAN ETNOBRA PADA SISWA SMP 1 CIRUAS - Hamidah, Hamidah; Kusuma, Jaka Wijaya; Auliana, Sigit (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
This dedication aims to explore the potential of ethnomathematical approaches and Geogebra software in introducing flat wake to SMP 1 Ciruas students. The ethnomathematical approach is used to relate mathematical concepts to the cultural context and daily life of students, while Geogebra as an interactive visual aid. The method of devotion used was an experiment with the design of the Training. Students of SMP 1 Ciruas became participants and participated in a series of learning using ethnomathematical and Geogebra approaches. At the end of the training, observation was carried out. The implementation of Community Service shows an increase in students' understanding of flat wake after the application of this approach. It is hoped that this method can be used as an alternative approach to learning mathematics that is more relevant and interesting for students, especially in the context of local culture